2014
DOI: 10.1007/s00210-014-0995-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of quercetin is unable to protect against isoproterenol cardiotoxicity

Abstract: Catecholamines are endogenous amines that participate in the maintenance of cardiovascular system homeostasis. However, excessive release or exogenous administration of catecholamines is cardiotoxic. The synthetic catecholamine, isoprenaline (isoproterenol, ISO), with non-selective β-agonistic activity has been used as a viable model of acute myocardial toxicity for many years. Since the pathophysiology of ISO-cardiotoxicity is complex, the aim of this study was to elucidate the effect of oral quercetin pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Calpain activated pathway may lead to contractile malfunctioning of heart, cytoskeleton damage, and cell death (Vanderklish & Bahr, ). Being a flavonoid, the major concern in clinical translation is the oral bioavailability as one of the study showed that oral administration of quercetin could not protect against ISP‐induced toxicity (Ríha et al, ). However, these ubiquitously available phytoconstituents should be used in regular diet to reduce the risk of CVDs.…”
Section: Natural Products and Their Pharmacological Potential In Allementioning
confidence: 99%
“…Calpain activated pathway may lead to contractile malfunctioning of heart, cytoskeleton damage, and cell death (Vanderklish & Bahr, ). Being a flavonoid, the major concern in clinical translation is the oral bioavailability as one of the study showed that oral administration of quercetin could not protect against ISP‐induced toxicity (Ríha et al, ). However, these ubiquitously available phytoconstituents should be used in regular diet to reduce the risk of CVDs.…”
Section: Natural Products and Their Pharmacological Potential In Allementioning
confidence: 99%
“…In some cases, it was reported that a higher dose of flavonoids such as rutin not only increased MI histopathological changes but also exacerbated the intensity of MI-related injuries. 15 For this reason, we decided to return this area and analyze the therapeutic effect of cur on experimental infraction in a model of rat induced by a synthetic β-adrenoreceptor antagonist namely isoproterenol hydrochloride (ISO). It seems that the results of the current experiment could pave a way to detect the possible advantages and drawbacks of distinct medicinal compound notably cur in the field of cardiovascular disease notably MI.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the promising effects of cur on cardiovascular disease, serious discrepancies, and opposite results have been previously shown in this area by numerous experiments. In some cases, it was reported that a higher dose of flavonoids such as rutin not only increased MI histopathological changes but also exacerbated the intensity of MI‐related injuries . For this reason, we decided to return this area and analyze the therapeutic effect of cur on experimental infraction in a model of rat induced by a synthetic β‐adrenoreceptor antagonist namely isoproterenol hydrochloride (ISO).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the complex pathophysiology, it is not surprising that no single agent can fully prevent/revert the injury caused by isoprenaline, or only works in low doses of isoprenaline . There are many reports showing that various natural compounds fully protect against isoprenaline cardiac injury in animal models, but it is not clear whether these studies have been performed according to the appropriate experimental standards …”
Section: Drugs With Possible Toxic Effects On Both Cardiomyocytes Andmentioning
confidence: 99%
“…103,[109][110][111][112][113][114] There are many reports showing that various natural compounds fully protect against isoprenaline cardiac injury in animal models, 115,116 but it is not clear whether these studies have been performed according to the appropriate experimental standards. 117,118 2 -agonists, when inhaled at therapeutic doses to treat bronchoconstriction, are considered to be relatively safe from the cardiovascular point of view; however, their selectivity is not absolute and in higher doses they also bind to 1 -receptors. As a consequence, vasodilation due to 2 -receptor stimulation can be accompanied tachycardia due to either reflex sympathetic activation or nonselectivity.…”
Section: Nonselective -Agonists and 2 -Agonistsmentioning
confidence: 99%